Arrhythmia burden, rhythm interventions and outcome in a large Swiss multicenter population of d-TGA patients with atrial switch. (19th May 2022) - Nozica, N; Asatryan, B; Aur, S; Greutmann, M; Schwerzmann, M; Bouchardy, J; Gass, M; Duru, F; Pascale, P; Reichlin, T; Pruvot, E; Wolber, T; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Patients with dextro-transposition of the great arteries (d-TGA) and atrial switch face a high life-time risk of arrhythmias. Purpose: To describe the incidence of arrhythmias, associated cardiac interventions and outcome in a large Swiss population of patients with d-TGA and atrial switch. Methods: In this multicenter analysis we included all consecutive patients with d-TGA and atrial switch treated at three Swiss tertiary care hospitals. The primary outcome was survival free from left ventricular assist device (LVAD), heart transplantation (HTx) and death. The secondary outcome was survival free from ventricular tachycardia, ventricular fibrillation and sudden cardiac death. Results: We identified 207 patients (34% females; median age at last follow-up 35 years) with d-TGA and atrial switch. Arrhythmias occurred in 97 patients (47%) at a median age of 22 years. A pacemaker or an implantable cardioverter/defibrillator was implanted in 39 (19%) and 13 (6%) patients, respectively, and 33 (16%) underwent a total of 51 ablation procedures to target 60 intra-atrial reentry tachycardias, 4 AV nodal reentry tachycardias and one atrial fibrillation (Figure 1). The primary outcome occurred in 21 patients (10%) and the secondary outcome in 18 (9%) (Figure 2). Primary and secondary outcomes were more common in patients with concomitant ventricular septum defect (VSD) than in those without (hazard ratio [HR] 3.06; 95% confidence interval [CI] 1.29-7.27, p=0.011; and HR 3.62; 95% CI 1.43-9.18, p=0.007, respectively). Conclusions: At a median age of 35 years, arrhythmias occur in almost half of patients with d-TGA and atrial switch and associated rhythm interventions are frequent. One in ten patients does not survive free from LVAD and HTx and outcome is worse in patients with concomitant VSD.